Population pharmacokinetic analysis of esomeprazole in Japanese subjects with various CYP2C19 phenotypes. (30th March 2020) - Nagase, Mario; Shimada, Hitoshi; Nii, Masahiro; Ueda, Shinya; Higashimori, Mitsuo; Ichikawa, Katsuomi; Zhang, Li; Zhou, Li; Chen, Yingxue; Zhou, Diansong; Dunyak, James; Al‐Huniti, Nidal
Abstract: What is known and objective: Esomeprazole, the S‐isomer of omeprazole, is a proton pump inhibitor which has been approved by over 125 countries, also known as NEXIUM ® . Esomeprazole was developed to provide further improvement on efficacy for acid‐related diseases with higher systemic bioavailability due to the less first‐pass metabolism and lower plasma clearance. Esomeprazole is primarily metabolized by CYP2C19. Approximately <1% of Caucasians and 5%‐10% of Asians have absent CYP2C19 enzyme activity. Although the influence of various CYP2C19 phenotypes on esomeprazole pharmacokinetics has been studied, this is the first report in the Japanese population where 27 low CYP2C19 metabolizers were included. Methods: In this study, a population PK model describing the PK of esomeprazole was developed to understand the difference of CYP2C19 phenotypes on clearance in the Japanese population. The model quantitatively assessed the influence of CYP2C19 phenotype on esomeprazole PK in healthy Japanese male subjects after receiving repeated oral dosing. The inhibition mechanism of esomeprazole on CYP2C19 activity was also included in the model. Results and discussion: CYP2C19 phenotype and dose were found as statistically significant covariates on esomeprazole clearance. The apparent clearance at 10‐mg dose was 17.32, 9.77 and 7.37 (L/h) for homozygous extensive metabolizer, heterozygous extensive metabolizer and poor metabolizer subjects, respectively. And the apparent clearance decreased as dose increased. What is new and conclusion: The established population PK model well described the esomeprazole PK and model‐predicted esomeprazole PK was in good agreement with external clinical data, suggesting the robustness and applicability of the current model for predicting esomeprazole PK. Abstract : CYP2C19 phenotype and dose were found as statistically significant covariates on esomeprazole clearance. The established population PK model well described the esomeprazole PK and was in good agreement with external clinical data.